A new genus and species of Cicadellini (Hemiptera: Cicadellidae) from China - Meng, Ze-Hong; Yang, Mao-Fa (Zootaxa, 2015)
The leafhopper genus Atkinsoniella was originally established by Distant (1908) for two species with A. decisa as type species. So far, 75 valid species are known worldwide and of these, 63 are from China (Yang et al. 2011). Because Atkinsoniella is a very large and morphologically heterogeneous genus it is desirable to recognize smaller groups of species with distinctive characteristics.